TRADISI LEDUG (LESUNG BEDUG) SURA DALAM PERSPEKTIF STRATEGI KENUSANTARAAN DI MAGETAN - Dea Lunny Primamona (Haluan Sastra Budaya, 2022)
This article aims to read the annual tradition of Ledug Sura in Magetan from an archipelagic strategy perspective. This study uses an archipelagic strategy perspective derived from a historical approach and a critical paradigm of cultural studies. The research uses several methods including: observation, interviews, archive studies, and literature studies. The results of this study indicate that the Ledug Sura tradition in Magetan was built by the history of Nusantara culture in Magetan and the process of revivalization. The layers of Magetan cultural history consist of three dimensions, namely: 1) Era of Civilization before and after Majapahit: 2) Mataram era civilization and colonialism; and 3) The era before independence until now. The reality of globalization has led to a process of revivalization of art which is expressed in a complex manner in the annual Ledug Sura ritual in Magetan. The revivalization is based on: 1) The spirit of cultural heritage as a form of respect for ancestral traditions; 2) The ideals of community unity and harmony; and 3) Construction of local cultural identity in the midst of globalization challenges.